(untitled) (MIST International Journal of Science and Technology, 2022)
This study describes the impact of the Padma Multipurpose Bridge in creating regional connectivity and mobility in traffic movement, thus contributing to the socioeconomic development of Bangladesh. It finds that the travel time between the Dhaka division and the southwestern region will be saved by about two hours for cars and buses and by over 10 hours for trucks due to new connectivity through the bridge. It will reduce the distance from Mongla Port to Dhaka by more than 100 km to 170 km and save a lot of working hours, which will further accelerate the growth of the country’s economy. Additionally, a total of 212.05 km of the new railway line is being constructed for the Padma Multipurpose Bridge, which will connect Dhaka with the country’s largest land port, Jessore. After the Padma Bridge Rail Link project is done, the travel time from Dhaka to Kolkata via Jessore will be cut in half, and it will take only 3 to 4 hours. Moreover, the bridge will also pave the way for putting in place a new route for the Trans-Asian Railway network. The Padma Multipurpose Bridge is estimated to boost the country’s annual GDP by 1.23 percent and the southwestern region’s GDP by 2.5 percent. Moreover, the Padma Multipurpose Bridge will reduce the poverty rate by 1.01 percent at the regional level and by 0.84 percent at the national level. This study finds that to take full advantage of the newly constructed bridge, the southern part of the outer ring road of Dhaka proposed in RSTP should be completed soon. Padma Multipurpose Bridge will work as a key component of Asian Highway-1, boosting economic growth in Asia and improving the country’s standing on the continent. MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 01-07